Reliability test and revision of stress coping scale for early childhood teachers - Jie Wang (Frontiers in Psychology)
The purpose of this research was to determine the reliability and validity of the Early Childhood Teachers’ Stress Coping Strategies Scale measured among early childhood teachers in Guangdong Province, China. The researcher used the Early Childhood Teachers’ Stress Coping Strategies Scale and a simplified version of the COPE questionnaire (Coping Inventory). The Early Childhood Teachers’ Stress Coping Strategies Scale consists of three dimensions: “Rational Thinking,” “Emotional Regulation,” and “Support Seeking,” and the simplified COPE questionnaire was consists of 2 dimensions: “Help Seeking” and “Cognitive Coping.” The scale was administered to 653 in-service ECE teachers and retested with a sample of 320 ECE teachers 1 month later. The internal consistency coefficient (ICC) of the questionnaire as a whole was 0.91, the internal consistency reliabilities of the 3 subscales ranged from 0.86–0.91, and the ICC values of the intragroup correlation coefficients of the latent variables ranged from 0.864–0.881, with a p < 0.05, which showed good reliabilities. Validity: exploratory factor analysis extracted a total of three factors with characteristic roots greater than 1. The three factors were denominated as, Rational Thinking, Emotion Regulation, and Support Seeking, and the three factors explained a total of 53.82% of the variance. The validation factor analysis showed that the model fit indices were GFI > 0.85, CFI > 0.9, NFI > 0.85, TLI > 0.9, IFI > 0.9, RMSEA<0.10, and RMR = <0.05, which indicated that the coping strategy scale with a good structural stability. Among the three-factor model, the discriminant and convergent validity of the three factors were reasonable. The correlation coefficients of rational thinking, emotion regulation, and support seeking with the two dimensions of help-seeking and cognitive coping in the COPE questionnaire were significantly positive and greater than 0.4, indicated that the correlation between this scale and the standardized scales was high. Overall, the Early Childhood Teachers’ Stress Coping Strategies Scale could be used for the measurement of early childhood teachers’ stress coping strategies.